Theoretical Estimations of Influence of Polymer Coatings on the Elastic Modulus and Ultimate Strength of Steel Samples - B.A. Garibyan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the model of a three-layer inhomogeneous strip and Voigt averaging are used to simulate the effective tensile modulus of the plates. To model the effective bending modulus of samples, the theory of bending of non-uniform beams is used. Good agreement was obtained between the calculated and experimental values of the elastic moduli determined in the tests for central tension and three-point bending. In this case, the calculation error does not exceed 5% for plates with a thickness of 1,5 mm and 10% for plates with a thickness of 0,7 mm. To assess the ultimate strength of the samples, an approximate estimate according to Voigt was used, which gives an error, in relation to experimental data, of the order of 10-15%, depending on the thickness of the steel substrate.